DEVELOPING TEACHING MATERIAL FOR DEBATE ACTIVITY IN SPEAKING CLASS - Sherly Citra Putri (Graduate Program, University of Islam Malang, 2020)
The aim of this study was to develop teaching material for debate activity in speaking class. The design of this research was Research and Development (R&D). The subject of this research were 27 students in 4th semester of English Department, Teacher Training and Education Faculty in Mayjend Sungkono University. The procedure of developing the teaching material for debate activity in speaking class was done through some steps adapted from Borg and Gall (1989). There were need analysis, material development, expert validation and revision, try out and revision, then product finalization. The researcher developed teaching material for debate activity in speaking class based on the interview to the lecturer and questionnaire to the students. The result ot the interview and questionnaire was used to develop teaching material for debate activity in speaking class before having validation from the experts. The material developed by adapting debate guidance from debate seminar and workshop, also from debate database book and guidance. The researcher added some parts of debate scripts examples, motion bank and debate website tournaments. There were 2 experts as validators. The first expert focused on the content of the product. The second validator focused on layout and the application of the product. After getting the validation and suggestions from both experts, the researcher revised the product.